Effectiveness of Using Virtual Reality Media for Students' Knowledge and Practice Skills in Practical Learning - Refdinal, Refdinal; Adri, Junil; Prasetya, Febri; Tasrif, Elfi; Anwar, Muhammad (Society of Visual Informatics, 2023)
Virtual Reality (VR) has become an option to be used as a learning medium in engineering. A study of the effectiveness of VR is needed to determine which fields and types of learning are suitable to employ it. This work aims to reveal the effectiveness of virtual reality media on students' cognitive and practice skills. The role of the media as a tool to make learning more efficient and effective. VR media brings learning in the virtual world that seems to be done in real terms. The research method used was a quasi-experiment with a posttest-only control group design research approach. The research subject consisted of two homogeneous classes. Learning outcomes are evaluated by testing students' cognitive and practice skills. The novelty of this research is the creation of learning media that are identical to the welding process simulator. Visual practice places and equipment in virtual form through VR are made to resemble practice places and equipment used in real situations. This similarity aims to provide concrete information about the welding process. The study revealed that the use of VR media significantly affected their knowledge. However, it did not significantly affect their practice skills. VR has not been able to provide an experience closer to real-life conditions during welding, such as heat, sparks, and sounds that appear when the electrode touches the workpiece. The distance between the electrode and the workpiece significantly affects the welding result in the welding process.